Influence of mineral interface stiffness on fracture propagation law of shale hydraulic fracturing - HOU Mengru,LIANG Bing,SUN Weiji,LIU Qi,ZHAO Hang (Youqicang pingjia yu kaifa)
In order to study the influence of mineral interface action on the initiation and propagation of shale hydraulic fracturing fractures, a shale microstructure model was established. In the model, the zero-thickness cohesive element was embedded in the solid element. A numerical simulation of the effect of mineral boundary interface stiffness on hydraulic fracture propagation was carried out to reveal the law of shale hydraulic fracturing crack propagation under the influence of mineral interface action. The results show that the tensile destruction is the main form of fracture failure of shale hydraulic fracturing. The crack propagation path consists of two ways, one is to extend along the mineral boundary, and the other is to cross the mineral boundary and enter the mineral to expand. With the increase of the mineral boundary interface stiffness, the crack initiation pressure and pore pressure gradually increase, the length, number and area of the cracks gradually decrease, and the width of the cracks gradually increases, so that it is easy to form short and wide cracks. When carrying out shale hydraulic fracturing operations, the location where the stiffness of the mineral boundary interface is lower should be selected first. The research results help to reveal the action mechanism of the mineral interface action on the expansion of the shale hydraulic fracture, and provide a theoretical basis for the reasonable selection of the hydraulic fracturing layer position of the shale gas reservoir.